2023
DOI: 10.3390/nano13010195
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Dielectric Nanopillar Antenna-Resonators for Efficient Collected Photon Rate from Silicon Carbide Color Centers

Abstract: A yet unresolved challenge in developing quantum technologies based on color centres in high refractive index semiconductors is the efficient fluorescence enhancement of point defects in bulk materials. Optical resonators and antennas have been designed to provide directional emission, spontaneous emission rate enhancement and collection efficiency enhancement at the same time. While collection efficiency enhancement can be achieved by individual nanopillars or nanowires, fluorescent emission enhancement is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…At the collective resonance point of these two moments (λ = 917 nm), we determined more than an order of magnitude decay rate enhancement with the maximum enhancement reaching 30. Such an enhancement has never been reported in dielectric neither in metal-dielectric individual nanopillars [38], thus paving the way for the use SiC metasurfaces to to enhance and control light extraction from quantum emitters, to study light matter interaction effects in integrated quantum photonics and for applications in quantum sensing. We also observed that by designing specific resonant structures, the coherent superposition of the ED and MQ moments can be used to better control the radiation/emission pattern and hence the emission directionality of the embedded dipole emitter compared to a single nanopillar.…”
Section: Discussionmentioning
confidence: 99%
“…At the collective resonance point of these two moments (λ = 917 nm), we determined more than an order of magnitude decay rate enhancement with the maximum enhancement reaching 30. Such an enhancement has never been reported in dielectric neither in metal-dielectric individual nanopillars [38], thus paving the way for the use SiC metasurfaces to to enhance and control light extraction from quantum emitters, to study light matter interaction effects in integrated quantum photonics and for applications in quantum sensing. We also observed that by designing specific resonant structures, the coherent superposition of the ED and MQ moments can be used to better control the radiation/emission pattern and hence the emission directionality of the embedded dipole emitter compared to a single nanopillar.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the spectral control engendered by surface plasmon resonance in metallic nanostructures, additional light routing effects can be achieved through wavelength-dependent scattering in conjunction with the effective reflection resulting from the placement of dielectric nano-pillars just above the pixel interface of image sensors. 36,37 In Fig. 2e, an SiN-based metalens array exhibits average optical efficiencies of 64%, 75%, and 94% at wavelengths of 430, 520, and 635 nm, respectively, through the entire RGB areas, which greatly exceed the upper limits of the optical efficiencies of the filter array for Bayer pixel arrangements (∼33%).…”
Section: Nanophotonic Spectral Sortingmentioning
confidence: 99%